(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Voluntary work is a practice of positive social behavior, a sense of responsibility and belonging to society. It expresses a distinctive wide-range character, based on social values and benign behaviors such as honesty, trust and cooperation, in this work individuals find themselves and seek to achieve their own interests. In this study, focus on the youth groups are the best age that can be attracted to volunteer work because it has positive behavioral dimensions at the psychological, spiritual and social level. The volunteer is able to acquirement new skills and experiences that return to his behavior and personality to reflect positively on his society.